1988
DOI: 10.1016/0014-5793(88)80771-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of structure of the initiator codon on translation in E. coli

Abstract: A set of plasmids carrying different initiator codons -either AUG, or GUG, or UUG, or CUG (as a control) in the hybrid gene IucIZ -was constructed by using synthetic oligonucleotides. GUG and UUG codons were demonstrated to be 2-3-times less effective than AUG in translation initiation. Furthermore, the correlation between the efficiencies of different initiator codons in translation initiation proved to vary, depending on the phase of bacterial growth. The rarely occurring usage in nature of the initiator cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…7B,C). Intriguingly, both corL and mgtM use the inefficient start codon UUG, which could be especially sensitive to global changes in translation, such as ribosome availability 37 . Because the majority of cytosolic Mg 2+ is devoted to maintenance of ribosome structure and activity, an increase in Mg 2+ uptake may help the cell cope with translational stressors 38 .…”
Section: Discussionmentioning
confidence: 99%
“…7B,C). Intriguingly, both corL and mgtM use the inefficient start codon UUG, which could be especially sensitive to global changes in translation, such as ribosome availability 37 . Because the majority of cytosolic Mg 2+ is devoted to maintenance of ribosome structure and activity, an increase in Mg 2+ uptake may help the cell cope with translational stressors 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in prokaryotes this triplet is fairly degenerate because, in addition to the most common "best-fit" AUG, other rare 3' or 5' wobbling codons (i.e., GUG, UUG, AUA, AUU) are occasionally found as translational starts. Changing these rare codons to AUG sometimes resulted in moderate (4,5) or large (6, 7) increases of expression, suggesting that the rare triplets may be used to slow down the expression of some select genes. The catalogue of genes starting with the rare triplets, which includes some of the most abundantly expressed genes in Escherichia coli, such as tufA (elongation factor Tu, ref.…”
mentioning
confidence: 99%
“…Mutagenesis of the UUG initiation triplet of the cyaA gene has shown that initiation codons UUG, GUG and AUG directed the synthesis of adenylate cyclase at relative levels of 1:2:6, respectively (28). In another case, lacZ translation from GUG and UUG (53) or AUC (54) codons instead of AUG was reduced two- to three-times; likewise, a truncated form of bacteriophage HB-3 murein hydrolase was synthesized in E. coli with an efficiency of 7.5 and 5% when instead of AUG the initiation codon was AUA and AUU or AUC (54). …”
Section: Resultsmentioning
confidence: 99%
“…For instance, the nature of the +2 codon was shown to be one of the determinants for the high translational efficiency of an mRNA beginning with UUG but not of a GUG start codon (62); likewise, a change in the initiation codon from AUG to AUA, which did not affect mRNA binding by ribosomes in the case of phage T7 0.3 gene (52), reduced the binding to the Qβ coat protein cistron to <10 and to 30% if the initiation triplet was followed by a G and by an A, respectively (63). Finally, the relative amounts of adenylate cyclase synthesized from initiation codons UUG, GUG and AUG is 1:2:6 when the triplets are located within the cyaA mRNA TIR but become 1:2:3 when the translation is driven from a lacZ fusion (53). …”
Section: Discussionmentioning
confidence: 99%